The neutrophil-to-lymphocyte and monocyte-to-lymphocyte ratios are independently associated with clinical outcomes of viral encephalitis - He, Qiang; Wang, Shuo; Chen, Haoan; Long, Lili; Xiao, Bo; Hu, Kai (Frontiers in Neurology, 2023)
Background: The neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) are used as prognostic biomarkers for many diseases. In this study, we aimed to explore the possibility of using ratios of NLR and MLR to predict the prognosis of viral encephalitis (VE). Methods: A total of 81 patients with an initial diagnosis of VE who were admitted to our hospital from January 2018 and January 2021 were retrospectively analyzed. Routine blood test within 24 h of admission was utilized to determine the ratios of NLR and MLR for each patient. The modified Rankin Scale (mRS) at 12 months after discharge was used to evaluate patents’ clinical prognosis, and the patients were divided into the group of good prognosis (mRS ≤ 1) and the group of poor prognosis (mRS ≥ 2) according to the mRS score. Univariate and multivariable regression analysis were used to differentiate and assess independent prognostic factors for the prognosis of VE. Results: NLR and MLR of poor prognosis group were significantly higher than that of good prognosis group. Multivariate logistic regression analysis results showed that NLR [odds ratio (OR): 1.421, 95% confidence interval (CI): 1.105-1.827; P < 0.05] and MLR [OR: 50.423, 95%CI: 2.708-939.001; P < 0.05] were independent risk factors for the poor prognosis of VE. NLR > 4.32 and MLR > 0.44 were suggested as the cut-off threshold for prediction of the poor prognosis of VE. Conclusion: NLR and MLR obtained from blood tests done at hospital admission has the potential to predict poor prognosis in patients with VE.